Current Therapy of Diabetic Macular Edema Bevacizumab, Triamcinolone Acetonide, and Laser Photocoagulation - Gladys Kusumowidagdo; Randy Sarayar; Kartika Rahayu; Gitalisa Andayani (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2019)
Background: Diabetic macular edema (DME) is the main cause of visual impairment in diabetic retinopathy (DR). Current gold standard therapy of DME is macular laser photocoagulation (MPC). Growing evidences have shown benefits of intravitreal anti-VEGF agents (i.e bevacizumab) and intravitreal corticosteroids (i.e triamcinolone acetonide). Aim: To compare the visual acuity (VA) improvement of patients with DME, treated with intravitreal bevacizumab (IVB), a combination of IVB and intravitreal triamcinolone (IVB/IVT), and MPC. Method: A comprehensive PubMedÂ® and CochraneÂ® databases search was conducted on May 4th, 2017 using appropriate keywords (diabetic macular edema, bevacizumab, triamcinolone, and laser photocoagulation using their MeSH terms). Studies were filtered using inclusion criterions (clinical trials, RCT, meta-analysis, systematic review, English, humans, and publication within 10 years) Results: Three studies (2 systematic reviews and 1 RCT) were found suitable. From these results, all studies showed favoring effects of IVB when compared to IVB/IVT combination and MPC in short term period (up to 6 months). However, there was no significant improvement of VA beyond this period in all groups. Conclusion: IVB appears to be superior to IVB/IVT and MPC in improving VA during 6 months follow- up period. Future systematic reviews and meta-analysis are required on the effect of IVB and MPC combination in cases of DME.